Exergoenvironmental analysis is a new tool for evaluation of an energy conversion system - Morosuk, T. (Енергетика і автоматика, 2015)
Exergy-based methods (exergetic, exergoeconomic and exergo-environmental analyses) are powerful tools for developing, evaluating and improving an energy conversion system. Exergoenvironmental analysis is a unique combination of exergy analysis and life cycle assessment conducted at the component level to identify the location, the magnitude and the causes of environmental impact.